Whole Genome-Based Characterization of Multidrug Resistant Enterobacter and Klebsiella aerogenes Isolates from Lebanon - Merhi, Georgi; Amayri, Sara; Bitar, Ibrahim; Araj, George F; Tokajian, Sima (Microbiology spectrum, 2023)
Enterobacter spp. and Klebsiella aerogenes are rod-shaped Gram-negative opportunistic pathogens. This study aimed at the molecular and genomic characterization of multidrug resistant Enterobacter spp. and K. aerogenes isolates recovered from hospitalized patients in a tertiary care hospital in Lebanon. A total of 59 Enterobacter spp. clinical isolates consisting of 41 carbapenem-resistant and 18 susceptible by Etest were included in this study. Genotypic identification through whole-genome sequencing (WGS) was performed and confirmed in silico. Resistance and plasmid profiles were studied using ResFinder4.0 and Plasmid-Finder2.1. Multilocus sequence typing (MLST) was used to determine the isolates' clonality. Using the average nucleotide identity (ANI) we identified and confirmed that 47 (80%) isolates were E. hormaechei, 11 (18%) were Klebsiella aerogenes and 1 (2%) was an E. cloacae. Carbapenem-resistance was detected among 41 isolates all showing an MIC90 of ≥ 32 μg/mL for ertapenem, imipenem, and meropenem. blaNDM-1 (58.5%), blaACT-16 (54%), and blaOXA-1 (54%) were the most common detected β-lactamases, while blaCTX-M-15 (68%) was the main detected extended-spectrum β-lactamase (ESBL) encoding gene. Chromosomal ampC, carbapenemase encoding genes, and porin modifications were among the detected carbapenem resistance determinants. The carbapenemase encoding genes were linked to three well-defined plasmid Inc groups, IncFII/IncFIB, IncX3, and IncL. MLST typing revealed the diversity within the studied isolates, with ST114 being the most common among the studied E. hormaechei.: The spread of carbapenem-resistant isolates in clinical settings in Lebanon is a serious challenge. Screening and continuous monitoring through WGS analysis could effectively limit the dissemination of drug-resistant isolates in hospitalized patients. IMPORTANCE Drug resistance is an increasing global public health threat that involves most disease-causing organisms and antimicrobial drugs. Drug-resistant organisms spread in health care settings, and resistance to multiple drugs is common. Our study demonstrated the mechanisms leading to resistance against the last resort antimicrobial agents among members of the Enterobacteriaceae family. The spread of carbapenem-resistant bacteria in clinical settings is a serious challenge. Screening and continuous monitoring could effectively limit the dissemination of drug-resistant isolates in hospitalized patients.
Keywords: Microbial Sensitivity Tests; Enterobacter; Humans; Enterobacter aerogenes; multidrug resistance; Multilocus Sequence Typing; Klebsiella aerogenes; karbapenemy; Klebsiella pneumoniae; mikrobiální testy citlivosti; lidé; ESBL; antibakteriální látky; bakteriální proteiny; beta-laktamasy; Anti-Bacterial Agents; Carbapenems; Lebanon; multilokusová sekvenční typizace; Bacterial Proteins; beta-Lactamases; β-lactamases; Libanon